Adipose-derived stromal cell therapy affects lung inflammation and tracheal responsiveness in guinea pig model of COPD. - Azadeh Feizpour; Mohammad Hossein Boskabady; Ahmad Ghorbani (PLoS ONE)
The effects of adipose derived stromal cells (ASCs) were evaluated on tracheal responsiveness and biochemical parameters in guinea pigs model of chronic obstructive pulmonary disease (COPD). Thirty six guinea pigs were divided into 6 groups including: Control, COPD, COPD+intratracheal delivery of PBS (COPD+ITPBS), COPD+intravenous delivery of PBS (COPD+IVPBS), COPD+intratracheal delivery of ASCs (COPD+ITASC) and COPD+intravenous injection of ASCs (COPD+IVASC). COPD was induced by exposing animals to cigarette smoke for 3 months. Cell therapy was then performed and after 14 days, tracheal responsiveness, concentration of interleukin-8 (IL-8) in serum and broncho-alveolar lavage fluid (BALF), as well as total and differential white blood cells (WBC) counts were evaluated. Tracheal responsiveness, total WBC counts, neutrophil and eosinophil percentage in BALF as well as concentration of IL-8 in serum and BALF significantly increased but lymphocyte percentage decreased in COPD compared to the control group (P<0.05 to p<0.001). Cell therapy was able to restore the tracheal hyper-responsiveness and the increased IL-8 concentration in serum and BALF of COPD-ITASC but not COPD-IVASC animals (P<0.05 for all cases). Total WBC in BALF also showed a significant decrease in both treated groups and the percentages of eosinophils, neutrophils and lymphocytes in BALF were reversed in COPD-ITASC compared to COPD-ITPBS animals (P<0.05 to P<0.001). Therefore, intratracheal cell therapy with ASC can decrease tracheal hyperresponsiveness and lung inflammation in cigarette smoke induced-COPD which may be helpful in attenuation of the severity of disease in patients suffering from COPD.